A novel Delay-based Adaptive Congestion Control TCP variant. (July 2022) - Verma, Lal Pratap; Sharma, Varun Kumar; Kumar, Mahesh; Kanellopoulos, Dimitris
Highlights: We developed a Delay-based Adaptive Congestion Control TCP variant (DACC). DACC has an initialization method that obtains an optimal initial value for the congestion window. It has a queueing-delay variation-based scheme that contemplates the contribution of all contention traffic flows. It has improved performance in goodput, throughput, file transfer time, and fairness. Abstract: Delay-based congestion control policies of the Transmission Control Protocol (TCP) mainly use the Round-Trip-Time (RTT) and bottleneck queue size to detect congestion. However, these policies identify congestion by only taking into account the contribution of their own data flow. Thus, the congestion identification in these policies fails to be completely accurate. Moreover, these policies experience many packet losses resulting in retransmissions, which can further reduce channel utilization. This article proposes a queuing delay variation-based adaptive congestion control TCP variant, called Delay-based Adaptive Congestion Control (DACC), that considers the presence of background flows. DACC quickly adapts to the current network conditions and adjusts the transmission rate accordingly. The simulation results exemplify the significance of DACC as it yields better outcomes in terms of goodput, Packet Loss Ratio (PLR), inter-protocol fairness, intra-protocol fairness, and fast file transfers. Graphical Abstract: Image, graphical abstract